Enhancing Critical Thinking: Integrating Guided Discovery Learning and Concept Mapping (GDL-CM) in Climate Change Concept - Diana Vivanti Sigit; Tsania Arrumaisha; Rizhal Hendi Ristanto (Jurnal Pendidikan IPA Indonesia, 2024)
Indonesia is confronted with the challenge of climate change, which adversely impacts students by diminishing their motivation to learn and causing various health problems. Addressing climate change requires an educational approach that emphasizes critical thinking skills, enabling students to comprehend,analyze, and devise solutions for these issues. This study analyzes the influence of the GDL-CM model on students' critical thinking skills on climate change material. This research is conducted at SMAN 36 Jakartai n January-May 2024. The research method used is a quasi-experiment and Nonequivalent Pretest-Posttest Control Group design. The study sample includes 62 students, with 31 students per class selected using a simple random sampling. The normalized gain value shows that the GDL-CM effectively improves critical thinking skills. Based on hypothesis testing using an independent t-test at α = 0.05 there is an influence of the GDL-CM learning model on students' critical thinking skills on climate change material. The influence is considered significant based on the effect size value. The results of this study imply that the GDL-CM learning model should be an alternative learning medium to develop critical thinking skills